LANDSCAPE AND FLOWERS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Development of landscape design based on the project of buildings constructed in this article. Correct choice of shape and type of flowers, bushes, lawns. Flower plants and flower beds made from them are today a separate field of phytodesign, serving for beautification of parks and cities.